Sculpture of Parshvanath Tirthankara - Temples of India Project Team (Jio Institute, 2024)
Sculpture of Parshvanath Tirthankara in the garbhagriha (sanctum sanctorum) of the Adinatha Temple. Carved in marble, the Tirthankara is shown seated in padmasana (lotus pose) and dhyan mudra (meditation posture). The pedestal has a carving of a snake.